Virtual business process management within collaborative manufacturing network: an implementation case. (9th March 2015) - Shamsuzzoha, Ahm; Helo, Petri T.
Business collaboration in the form of virtual factory is nowadays considering as one of the critical factor in the manufacturing community, mostly within small and medium size enterprises (SMEs). In such an environment, it is very important to deal with accompanying process details within virtual factory environment. This research articulates fundamental concepts of the virtual business network in the form of plug-and-play virtual factory, where both intra and inter-organisational processes are defined for the purpose to execute the virtual collaboration successfully. Different phases of virtual factory and its associated process steps are defined with necessary annotations. All such business processes as required to execute the virtual factory are exclusively presented with examples. More specific example of the virtual factory monitoring and controlling process is illustrated and highlighted with the help of user interface portal known as dashboard. The functionality and importance of this dashboard user interface layer is presented with its inherent features and implementation perspectives. This paper is concluded with future research directions.